Banning Political Work on Judges is a Guarantee of Human Rights - Kadhim, Mohammed Hasan; Auda, Khaled Kadhem (International Journal of Psychosocial Rehabilitation, 2020)
The judiciary is the authority that individuals resort to when their rights , freedoms are exposed to danger, and the matter is settled for those who are exposed to the rights and freedoms of individuals, whether it is ordinary individuals or other state authorities, especially the multiple executive branches of the authority, the authority of the judiciary also extends to adjudicating cases that arise between the authorities of the other state among themselves, so that the judiciary is the one with jurisdiction to protect rights and freedoms, as well as the importance of the role played by the judiciary, the matter requires that, this authority enjoys complete independence. Perhaps one of the most important elements of independence is the reluctance of members of that authority from engaging in political work because of that reason leading to many deviations on the course of judicial work as a result of political pressure that happen to judges when they belong to parties or other political institutions, due to the seriousness of this and its significant effects on human rights, most constitutional regimes were keen to attend political work for judges.